123k views
2 votes
Solve -37 + n = -56 for n. -93 -19 19 93

User Kivul
by
5.8k points

2 Answers

5 votes

Answer:

n=-93

A. -93 *(first option)*

Explanation:

First, you subtract by 37 from both sides of equation.

-37+n-37=-56-37

Then, simplify to find the answer.

-56-37=-93

n=-93 is the correct answer.

I hope this helps you, and have a wonderful day!

User Arav
by
6.2k points
4 votes

Answer:

n = -19

Explanation:


-37+n=-56\qquad\text{add 37 to both sides}\\\\-37+37+n=-56+37\\\\n=-19

User Rolando Yera
by
6.2k points